2010
DOI: 10.2463/mrms.9.141
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI Predict Local Control Rate of Uterine Cervical Cancer Immediately after Radiation Therapy?

Abstract: Purpose: To evaluate the utility of measuring the volumes of areas of high signal intensity on T 2 -weighted magnetic resonance (MR) images immediately after irradiation for predicting the local control rate of uterine cervical cancer.Materials and Methods: From our departmental database, we identiˆed 109 patients with cervical cancer who underwent MR imaging before irradiation and just before or just after completion of radiation therapy from 1994 to 2007. We included 46 of the 109 patients in this study, 5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Several groups have performed semi-objective volumetric tumor measurements for the assessment of treatment responses [ 10 13 , 20 , 21 ]. Most of these studies were performed retrospectively with small study populations, the imaging protocols employed differed from study to study, and volume evaluations were obtained using ellipsoid based volume measurements, which are inferior to those obtained by manual and freehand delineation of regions of interest [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have performed semi-objective volumetric tumor measurements for the assessment of treatment responses [ 10 13 , 20 , 21 ]. Most of these studies were performed retrospectively with small study populations, the imaging protocols employed differed from study to study, and volume evaluations were obtained using ellipsoid based volume measurements, which are inferior to those obtained by manual and freehand delineation of regions of interest [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the promising results as a predictor of response, larger studies are needed because their series only included 25 cases. In this sense, Saida et al [24] studied a series of 46 cases measuring the volume of the areas of high signal intensity in T2 immediately after finishing the treatment. They concluded that local control depends more on the diminishment of volume registered than the initial volume.…”
Section: Mri 3 Monthsmentioning
confidence: 99%
“…Hricak et al (80) reported that the finding of reconstitution of the normal zonal anatomy of the cervix and the presence of homogenous low‐signal‐intensity cervical stroma are reliable indicators that the cervix is normal after 3–6 months of radiation therapy (RT). Saida et al (81) evaluated the local recurrence rate by measuring the volumes of areas of high signal intensity on T2‐weighted images just before/after RT. The patients with local recurrence had larger areas of high signal intensity on T2‐WI just before/after RT than those without recurrence (81).…”
Section: Role Of Mri In Decision Makingmentioning
confidence: 99%
“…Saida et al (81) evaluated the local recurrence rate by measuring the volumes of areas of high signal intensity on T2‐weighted images just before/after RT. The patients with local recurrence had larger areas of high signal intensity on T2‐WI just before/after RT than those without recurrence (81). However, these findings were not satisfactory for predicting the patient's prognosis.…”
Section: Role Of Mri In Decision Makingmentioning
confidence: 99%